Knowledge, attitudes and habits regarding oral health among nurses of Clinical hospital center Rijeka Znanja, navike i stavovi medicinskih sestara / tehničara Kliničkog bolničkog centra Rijeka o oralnom zdravlju - Ivančić Jokić, Nataša; Bakarčić, Danko; Cicvarić, Odri; Šimunović Erpušina, Marija; Zukanović, Amila; Hefler, Gordana; Nastić, Vendi (2021)
Background/Aim: The aim of this study was to investigate oral health knowledge, attitudes and habits regarding oral health among nurses and to evaluate if there is a difference in self-reported oral health behavior in relation to the degree of professional education. Methods: The study was conducted on a sample of 100 subjects, both gender, aged 22 to 62. The respondents were nurses with completed secondary school (49%) and nurses with bachelor"s or master"s degrees in nursing (51%). The study was conducted via the Croatian version of the Hiroshima University-Dental Behavioral Inventory (HU-DBI) questionnaire. Results: Nurses with a bachelor"s or master"s degree had a significantly higher HU-DBI score than nurses with completed secondary school (p=0.033). Statistically significant difference was found in the following questions: I brush each of my teeth carefully (p=0.026), I put off going to the dentist until I have a toothache (p=0.008) and I have had my dentist tell me that I brush very well (p=0.016). Conclusion: The obtained results show that healthcare professionals with higher education (bachelor"s or master"s degree in nursing) have more knowledge on oral health and that they apply this knowledge in their daily oral hygiene routine.
Uvod/cilj: Cilj je ovog istraživanja ispitati stupanj znanja i stavove o oralnom zdravlju medicinskih sestara, prvostupnica/prvostupnika i magistri/magistara sestrinstva, zaposlenih u KBC-u Rijeka, te vidjeti postoje li razlike u znanju i stavovima u odnosu na stupanj stručne spreme. Ispitanici i metode: Istraživanje je provedeno na uzorku od 100 ispitanika muškog i ženskog spola, u dobi od 22 do 62 godine. Ispitanici su medicinske sestre sa završenom srednjom školom (49 %) i prvostupnici ili magistri sestrinstva (51 %). Istraživanje je provedeno putem upitnika Hiroshima University-Dental Behavioral Inventory (HU-DBI). Rezultati: Medicinske sestre / medicinski tehničari koji su prvostupnici ili magistri sestrinstva imaju statistički značajno viši ukupan HU-DBI (p = 0,033). Statistički značajne razlike nađene su u pitanjima o pažljivom četkanju svakog zuba (p = 0,026), o odgađanju odlaska stomatologu sve dok ne zaboli zub (p = 0,008) i o tome da im se dogodilo da im stomatolog kaže da dobro četkaju svoje zube (p = 0,016). Zaključak: Dobiveni rezultati pokazuju da medicinske sestre sa završenim studijem sestrinstva imaju više znanja o oralnom zdravlju i da ta znanja primjenjuju u svom svakodnevnom održavanju oralne higijene
Bibliografija
Summary.
Keywords: medicinske sestre, oralno zdravlje, stavovi zdravstvenih djelatnika